Analisis Fundamental Makro dan Fundamental Mikro Terhadap Nilai Perusahaan Dengan Struktur Modal, Kinerja Keuangan, dan Struktur Kepemilikan Dengan Variabel Intervening Pada Perusahaan Makanan dan Minuman Yang Terdaftar di BEI - Selma Nevira Shinta Putri; Hwihanus Hwihanus (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research aims to analyze the influence of macro and micro fundamental factors on company value with capital structure, financial performance and ownership structure as intervening variables. This research uses a purposive sampling method with the help of Smart PLS 4 software. The data source used in this research is secondary data, namely the annual financial reports of food and beverage companies for 2020-2022 obtained from the official IDX website or obtained directly from the company website. The results of this research show that there are 8 hypotheses that are rejected and 5 hypotheses that are accepted. Macro fundamentals do not have a significant effect on capital structure, financial performance, ownership structure, company value. Micro fundamentals have a significant effect on financial performance, capital structure and company value.